Wood-steel composite shear walls with openings - Vogiatzis, Tzanetis; Tsalkatidis, Themistoklis; Avdelas, Aris (International Journal of Engineering and Technology, 2020)
This paper reports an investigation into the behaviour of wood-steel composite shear walls, consisting of strand laminated lumber boundary frames with infill steel plates. Recently it has been shown that wood-steel composite shear wall systems can offer various advantages over code-approved wood frame shear walls, including architectural flexibility. However, further research is needed so as to gain a better insight and understanding into the structural behaviour of this lateral load resisting system. On this basis, three-dimensional full-scale finite element models are developed and used to simulate the wood-steel composite shear wall with solid infill plates and with centrally-perforated infill plates. In this paper, firstly, a three-dimensional finite element model of wood-steel composite shear wall under monotonic loading. The numerical results were compared with experimental data and it was found that the model can predict the behaviour of wood-steel composite shear walls with reasonable precision. Using the verified model, a parametric study on wood-steel composite shear wall models with and without openings was performed. Critical parameters influencing the wood-steel composite shear walls behaviour such as the thickness of the steel plate and the opening ratio were investigated. The results of this parametric study provide useful information for the engineering application of wood-steel composite shear wall systems.Â Â